145k views
2 votes
What is n in the equation -5(1+6n)=5n-5?

User GigiSan
by
4.7k points

1 Answer

2 votes

Answer:

0 is your answer

Explanation:

Note the equal sign, what you do to one side, you do to the other. Remember to follow PEMDAS.

First, distribute -5 to all terms within the parenthesis

-5(1 + 6n) = (-5)(1) + (-5)(6n) = -5 - 30n

-30n - 5 = 5n - 5

Isolate the variable, n. Subtract 5n and add 5 to both sides

-30n (-5n) - 5 (+5) = 5n (-5n) - 5 (+5)

-30n - 5n = -5 + 5

-35n = 0

Isolate the n, Divide -35 from both sides

(-35n)/-35 = (0)/-35

n = 0

0 is your answer

~


User DrEarnest
by
6.0k points